Advanced clinical practitioners' inter-shift need for recovery: a cross-sectional survey in emergency medicine. (21st July 2022) - Fenwick, Rob; Price, Rebecca; Kershaw, Tanya; Boddy, Rachael; Chessum, Peter
Abstract : Background: Healthcare settings are high-risk environments for fatigue and staff burnout. The Need For Recovery (NFR) scale quantifies inter-shift recovery, which contributes to cumulative fatigue and may precede occupational burnout. Advanced clinical practitioners (ACPs) are an established feature of the emergency medicine workforce in the UK, however, little is known about factors affecting their inter-shift recovery, fatigue or how NFR correlates with formal burnout inventories. Methods: A prospective cross-sectional online survey of UK emergency medicine ACPs from 1 September to 30 September 2020. The primary aim was to determine the NFR of these ACPs. The secondary aims were to determine any statistical associations between NFR and selected variables, and whether NFR could reliably predict burnout using the Copenhagen Burnout Inventory (CBI) as a comparator. Results: There were 529 responses to the survey from 50 sites (response rate: 88%). The median NFR was 63.6 (95% CI 54.5–63.6). Lower NFR scores were found in ACPs who see both adults and children (54.5, 95% CI 45.4-63.6), work shifts of 7–10 hours (54.5, 95% CI 36.3–63.6) and who found it easy to park before work (54.5, 95% CI 45.5–54.5). Linear regression modelling indicated significant associations between shift length, ease of parking, ability to get breaks and feeling overwhelmed. Spearman's rho between NFR and CBI for personal and work-related burnout was 0.741 and 0.766 respectively. Correlation between NFR and patient-related burnout was less at 0.471. Conclusion: This study has shown the second highest NFR score reported in any occupational group. Several factors have been identified that may potentially reduce NFR and could be changed by organisations. NFR could also be used to identify those suffering with occupational burnout.